An inventory of simple monetary policy rules in a new Keynesian macroeconomic model - Thomas A. Lubik; Massimiliano Marzo (The Johns Hopkins University, Department of Economics, 2003)
We derive necessary and suffcient conditions for simple monetary policy rules that guarantee equilibrium determinacy in the New Keynesian monetary model. Our modeling framework is derived from a fully specified optimization model that is still amenable to analytical characterisation. The monetary rules analyzed are variants of the basic Taylor rules ranging from simple inflation targeting (current, forward, backward), to the canonical Taylor rules with and without inertial nominal interest rate patterns. We establish that determinacy obtains for a wide range of policy parameters, especially when the monetary authority targets output and smoothes interest rates. Contrary to other results in the literature we do not find a case for super-inertial interest rate policy
Keywords: C62; E40; E52; 330; Taylor Rule; Monetary Policy; Indeterminacy; New Keynesian; Geldpolitik; Regelgebundene Politik; Taylor-Regel; Neukeynesianische Makroökonomik; Theorie